2020
DOI: 10.1093/jme/tjaa103
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Mosquitoes of Pará State in the Brazilian Amazon: Species Composition, Habitat Segregation, and Seasonal Variation

Abstract: Mosquitoes (Diptera: Culicidae) are one of the most important disease vector species in the world. Many species have a high degree of anthropophilia and are often found in human habitations. In the present study, we have inventoried the nocturnal mosquito assemblage in intra-, peri-, and extradomicile environments in four municipalities in Pará, Brazil. At each municipality, a residence was selected and the mosquitoes were sampled using the protected human attraction capture and Shannon trap methods in April (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…Entomological inventories conducted in the Amazon basin have already recorded the six species of Mansonia that are in the present study ( Ferreira 1999 , 2003 ; Hutchings et al 2008 , 2020 ). The greater diversity and abundance of the genus Mansonia has been reported in the areas close to white-water lakes or muddy rivers ( Ferreira 1999 , Araújo et al 2020 ), as compared to dark water rivers, such as the Negro River ( Hutchings et al 2005 , 2013 , 2016 ). The Madeira River, characterized as a white-water river, is the largest tributary of the Amazon River basin, which is characterized by a high load of suspended sediments, alone being responsible for approximately 50% of the total suspended load transported along the Amazon River to the Atlantic Ocean ( Latrubesse et al 2005 , Barbosa et al 2007 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Entomological inventories conducted in the Amazon basin have already recorded the six species of Mansonia that are in the present study ( Ferreira 1999 , 2003 ; Hutchings et al 2008 , 2020 ). The greater diversity and abundance of the genus Mansonia has been reported in the areas close to white-water lakes or muddy rivers ( Ferreira 1999 , Araújo et al 2020 ), as compared to dark water rivers, such as the Negro River ( Hutchings et al 2005 , 2013 , 2016 ). The Madeira River, characterized as a white-water river, is the largest tributary of the Amazon River basin, which is characterized by a high load of suspended sediments, alone being responsible for approximately 50% of the total suspended load transported along the Amazon River to the Atlantic Ocean ( Latrubesse et al 2005 , Barbosa et al 2007 ).…”
Section: Discussionmentioning
confidence: 98%
“…This was also observed in the populations of Ma. titillans in the State of Pará ( Araújo et al 2020 ). In addition, our data highlights the abundance of Mansonia spp.…”
Section: Discussionmentioning
confidence: 99%
“…leucocelaenus during the rainy season in a study in the state of Rio de Janeiro carried out in the Ecological Reserve of Guapiaçu. In a study in the Amazon, [ 39 ] found higher abundance and richness of mosquitoes in the rainy season compared to the dry season, with Hg . leucocelaenus only present during the rainy season.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of mosquito fauna in these ecosystems are in general limited to sampling in a single month within the rainy season (e.g. Araújo et al 2020; Rêgo et al, 2020; Santos et al, 2015). We strongly suggest that this unique mosquito sampling should occur only a few weeks after a large amount of rain is recorded.…”
Section: Discussionmentioning
confidence: 99%